2009
DOI: 10.2337/db08-1266
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Postnatal Growth Increases Lipogenic Gene Expression and Adipocyte Size in Low–Birth Weight Mice

Abstract: OBJECTIVE To characterize the hormonal milieu and adipose gene expression in response to catch-up growth (CUG), a growth pattern associated with obesity and diabetes risk, in a mouse model of low birth weight (LBW). RESEARCH DESIGN AND METHODS ICR mice were food restricted by 50% from gestational days 12.5–18.5, reducing offspring birth weight by 25%. During the suckling period, dams were either fed ad libitum, permitting CUG in offspring, or food restricted, preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 51 publications
5
73
1
Order By: Relevance
“…The difference between the two diets may affect fat storage in the mothers and modify fat content in the milk during suckling. In fact, the catch-up growth in the other model has been recently shown to be associated with increased gonadal fat, lipogenic gene expression and adipocyte size [20], whereas our adult animals showed decreased adiposity. Alternatively, the differences observed between the two models may also arise from the duration of food restriction, which in our model starts 1 day earlier [19].…”
Section: Discussionmentioning
confidence: 90%
“…The difference between the two diets may affect fat storage in the mothers and modify fat content in the milk during suckling. In fact, the catch-up growth in the other model has been recently shown to be associated with increased gonadal fat, lipogenic gene expression and adipocyte size [20], whereas our adult animals showed decreased adiposity. Alternatively, the differences observed between the two models may also arise from the duration of food restriction, which in our model starts 1 day earlier [19].…”
Section: Discussionmentioning
confidence: 90%
“…The studies to date have reported increased fat accumulation after catch-up growth in low birthweight infants and in animal models of IUGR [30,31] . Previous studies in rats have demonstrated that the majority of body fat is located in subcutaneous deposits at the time of weaning (subcutaneous fat weight increases 6-fold).…”
Section: Discussionmentioning
confidence: 99%
“…Placental inflammation is a characteristic of maternal obesity, a risk factor for obesity in offspring, and involves inflammatory macrophage infiltration that can alter the maternal-fetal circulation (74). Inflammatory disturbances in the placenta may alter the nutrient set points established early in life and predispose to an accelerated pattern of catch-up growth that contributes to the risk for later obesity, especially in low-birth-weight infants (75,76). The concept that inflammatory networks can influence the predilection toward obesity is supported by the find-ings that variation in obesity susceptibility between mouse strains is intrinsically linked to the inflammatory networks and leukocyte composition of adipose tissue established prior to HFD exposure (77).…”
Section: Figurementioning
confidence: 99%